2005
DOI: 10.1073/pnas.0501526102
|View full text |Cite|
|
Sign up to set email alerts
|

Diverse taxa of cyanobacteria produce β- N -methylamino- l -alanine, a neurotoxic amino acid

Abstract: Cyanobacteria can generate molecules hazardous to human health, but production of the known cyanotoxins is taxonomically sporadic. For example, members of a few genera produce hepatotoxic microcystins, whereas production of hepatotoxic nodularins appears to be limited to a single genus. Production of known neurotoxins has also been considered phylogenetically unpredictable. We report here that a single neurotoxin, β- N -methylamino- l -alanine, may be produced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
443
4
12

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 638 publications
(492 citation statements)
references
References 28 publications
7
443
4
12
Order By: Relevance
“…BMAA, originating from cyanobacterial cycad root symbionts of the genus Nostoc, was demonstrated to bioaccumulate at various trophic levels including in some of the traditional foods of these inhabitants of these islands (Cox et al 2003). However, recently Cox et al (2005) revealed that BMAA production by cyanobacteria appeared most likely to be a general phenomenon, as BMAA was detected in 95% of 21 cyanobacterial genera. Indeed, most recent GC-MS/MS analyses of Aph.…”
Section: Demonstrated the Uptake Of [ 3 H]-dihydro-microcystin-lr Inmentioning
confidence: 99%
See 4 more Smart Citations
“…BMAA, originating from cyanobacterial cycad root symbionts of the genus Nostoc, was demonstrated to bioaccumulate at various trophic levels including in some of the traditional foods of these inhabitants of these islands (Cox et al 2003). However, recently Cox et al (2005) revealed that BMAA production by cyanobacteria appeared most likely to be a general phenomenon, as BMAA was detected in 95% of 21 cyanobacterial genera. Indeed, most recent GC-MS/MS analyses of Aph.…”
Section: Demonstrated the Uptake Of [ 3 H]-dihydro-microcystin-lr Inmentioning
confidence: 99%
“…containing BGAS demonstrated large quantities of BMAA (Dietrich unpublished data). If BMAA is indeed involved in the aetiology of ALS/PDC, the findings of BMAA in BGAS may potentially explain the detection of BMAA in brain tissues of Canadians with Alzheimer's disease (Cox 2005). Although it would have to be established whether or not these patients had consumed BGAS at any given time.…”
Section: Demonstrated the Uptake Of [ 3 H]-dihydro-microcystin-lr Inmentioning
confidence: 99%
See 3 more Smart Citations